Anticancer-active 3,4-diarylthiolated maleimides synthesis via three-component radical diarylthiolation - Wang, Limei; Li, Zhuo; Ma, Zhehan; Xia, Kedi; Wang, Wenyu; Yu, Wenchang (Frontiers in Chemistry, 2022)
Herein, we report an efficient and simple copper-catalyzed oxidative diarylthiolation of maleimides with sulfur powder and aryl boronic acids, in which S powder was used as a substrate and internal oxidant. The corresponding double C-S bonds coupling products were obtained in moderate to high yields under a simple catalytic system. Mechanistic studies indicated that copper-catalyzed radical thiolation of aryl boronic acids with S powder, and the resulting arylthiyl underwent radical addition with double bonds of maleimides.